FIVE-FINGER'S HYPNOTHERAPY ON ACADEMIC STRESS LEVELS IN ADOLESCENTS AT TAHFIDZ KHAIRUNNAS TUBAN - Nur Faizah, Hanim; Oktodia Basuki , Hyan; Suhartono, Suhartono; Widyawati, Mei; Pitaloka, Dyah (Lux Mensana: Journal of Scientific Health, 2023)
Introduction: Academic stress is a condition where there is a mismatch between academic demands and abilities. Students dealing with the burden of lessons that are considered quite heavy at school will be able to cause stress to adolescents at this time, adolescents generally experience pressure from the school and sometimes from parents demanding children to get high grades. Non-pharmacological therapy is a type of treatment/prevention that has no impact/effect on internal organs compared to pharmacological therapy which uses drugs. One of the non-pharmacological treatments that can reduce academic stress is Five-finger’s hypnotherapy, Five-finger’s hypnosis is a form of self-hypnosis that can have a high relaxation effect, thereby reducing anxiety, tension, and stress. This study aims to determine the effect of Five-finger’s hypnotherapy on the level of academic stress in seventh-grade adolescents at Tahfidz Entrepreneur Junior High School, Khairunnas Tuban. Methods: This type of research is pre-experimental using a one-group pre-post test design approach with a cohort approach. The instrument used in this study was the academic stress questionnaire. The population in this study was 102 adolescents who were selected by a simple random sampling technique, obtaining 81 adolescents. The Inclussion criteria: Class VII youth of SMP Tahfidz Entrepreneur Khairunnas Tuban and Willing to be a respondent. The independent variable in this study is five-finger’s therapy and the dependent variable is academic stress. Result & Analysis: The results of the research conducted after being analyzed using the Wilcoxon test with a significance level of =<0.05 was proven to reduce the level of academic stress with a value of = 0.000<0.05 which means that H1 is accepted, namely there is an effect of five finger`s hypnotherapy on the level of academic stress in students VII graders. Discussion: From the description above, it can be concluded that five finger hypnotherapy affects reducing academic stress levels in seventh-grade adolescents at Tahfidz Entrepreneur Junior High School, Khairunnas Tuban.